(untitled) (KYAMC Journal, 2021)
The severe acute respiratory syndrome (SARS) caused by the super-infectious, super-spreading, super-mutating novel coronavirus-2 (Covid-19) is responsible for the worldwide overwhelming panic and pandemic with a huge burden of suffering patients at a time. It has been causing alarming morbidity and unexpected mortality, shortening life span of many people that hadn’t happened since the second world war. It was first identified in Wuhan, China in the last months of 2019. The clinical scenario presents in the form of asymptomatic, mild, moderate and severe illnesses. More than 80% patients are either asymptomatic who transmit it to others and have a mild influenza-like illness clinically not different from common cold. The moderate and severe cases commonly need supervised home or institutional treatment. Many of the latter need intensive therapy that includes non-invasive and invasive ventilation along with other measures and medications. The treatment is principally conservative, HDU- and ICU-dependent. Surgery has no role as its primary treatment. But protection of surgical team and non-infected patients remains as a challenge to surgeons and hospital authorities. Many of the mutant variants now show resistance to antibodies generated by spike protein based and m-RNA based vaccines. The threat of infection still persists making surgeons overwhelmingly concerned while performing emergency, elective and cancer surgeries. This article describes some guidelines to be followed by the operating surgeons, hospital and regional health authorities to minimize the risks of spreading the disease and to protect the surgical team and other non-infected people from being infected. KYAMC Journal. 2021;12(3): 172-181